Management of Positive Sub‐areolar/Nipple Duct Margins in Nipple‐Sparing Mastectomies. Issue 4 (2nd June 2014) - Camp, Melissa S.; Coopey, Suzanne B.; Tang, Rong; Colwell, Amy; Specht, Michelle; Greenup, Rachel A.; Gadd, Michele A.; Brachtel, Elena; Austen, William G.; Smith, Barbara L.
Abstract We evaluated management of positive sub‐areolar/nipple duct margins in nipple‐sparing mastectomies (NSM) at our institution. Retrospective chart review of all NSM from January 2007 to April 2012 was performed and patient, tumor, and treatment information was collected. Sub‐areolar/nipple duct margins included ductal tissue from within the nipple. Of 438 NSM, 22 (5%) had positive sub‐areolar/nipple duct margins; 21 of 220 cancer‐bearing breasts (10%) and 1 of 218 prophylactic mastectomies (0.5%). Positive margins included four with invasive lobular carcinoma and 18 with ductal carcinoma in situ (DCIS). Management included removal of eight nipples and nine nipple areola complexes (NAC). Four of 17 nipple/NAC specimens had evidence of residual DCIS and none had residual invasive cancer. The majority of nipple/NAC specimens excised for a positive margin had no residual malignancy. Future studies are needed to determine the extent of NAC tissue removal required for positive margins.